KH. MUHAJIRIN AMSAR CONTRIBUTION ON LEGAL HADITH INTERPRETATION - Hakim, Masykur (UIN Ar-Raniry, 2015)
The word Ã¢â‚¬ËœcontributionÃ¢â‚¬â„¢ is originally derived from English word which means to help orÃ‚Â donations, for example Ã¢â‚¬Å“His contribution to art literature was very great, which meansa very large contribution to the literature.Or a meaningful contribution to charity which equal understanding to donations to charity.Furthermore, etymologically speaking the word Ã¢â‚¬ËœsharhÃ¢â‚¬â„¢ (interpretation) is derived from the Arabic sharaha which meansÃ¢â‚¬Ëœto explainÃ¢â‚¬â„¢, Ã¢â‚¬Ëœto openÃ¢â‚¬â„¢, Ã¢â‚¬Ëœto paveÃ¢â‚¬â„¢.Ã‚Â And too, the wordÃ‚Â Ã¢â‚¬ËœsharhÃ¢â‚¬â„¢ is usually used to describe the meaning of the hadith, while the word Ã¢â‚¬ËœtafsirÃ¢â‚¬â„¢ is usually used to explain the meaning of the Qur'an.Ã‚Â Ã‚Â For the impelementation, the word tafsiris exclusively concerning with the interpretationof the qur'anic meaning.Ã‚Â While sharh, relies on hadith interpretation, its content, conclusion (istinbath) for bothlegalormoralof the ProphetÃ¢â‚¬â„¢s words, or explaining other disciplines.